Early Emphysema in Patients with Anorexia Nervosa - Coxson, Harvey O; Chan, Ida H. T; Mayo, John R; Hlynsky, Julia; Nakano, Yasutaka; Birmingham, C. Laird (American journal of respiratory and critical care medicine, 2004)
Postmortem studies of patients who died in the Warsaw Ghetto during World War II suggested that death from starvation was associated with pulmonary emphysema. This study re-examines this hypothesis in patients who are chronically malnourished because of anorexia nervosa. Age, smoking history, body mass index, and pulmonary function were measured in 21 subjects with anorexia nervosa and 16 control subjects. Computed tomography (CT) scans were obtained from three regions of the lung (at the level of the aortic arch, the carina, and the posterior position of the eighth rib) using a multislice scanner. The CT measurements of lung density, emphysema, and surface area-to-volume ratio were obtained using the X-ray attenuation values. CT measurements of emphysema were greater in the group that was anorexic than in historical control subjects (p < 0.001). Furthermore, there were significant correlations between the body mass index and the CT measures of emphysema for all the patients and between diffusing capacity and the CT measurements in the patients who were anorexic. A multiple linear regression analysis showed the diffusing capacity was predicted best by the percentage of lung voxels within the large emphysematous changes category. These data demonstrate that emphysema-like changes are present in the lungs of patients who are chronically malnourished.